What Katy Did - Coolidge, Susan; Illustrated by Reed, Neil (London Puffin Books, 1995)
Despite her best intentions, quick-tempered Katy Carr's efforts to be tidy and good-tempered always seem to land her in trouble. Then, one terrible day, Katy has an accident, but it is still a long, eventful time before she learns to be as loving and as patient as her beautiful invalid cousin Helen.
Include Illustrations
Keywords: Families -- Fiction